Self-rated health status and lifestyle factors: A cross-sectional study of human and natural science educators - Monteiro, Pâmela Vieira; Neves, Gabriela Silvério das; Cruz, Geise Ferreira da; Cattafesta, Monica; Rica, Roberta Luksevicius; Ferraz, Almir de França; Junior, Aylton Figueira; Viana, Michell Vetoraci; Shimojo, Guilherme Lemos; Salaroli, Luciane Bresciani (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Self-rated health status is a subjective indicator that is based on the body’s perception of health status, covering personal components such as, physical aspects, aspects of general well-being and satisfaction with life. Objective: To analyze the self-rated health status and factors associated with the lifestyle of higher education educators. Material and methods: This is an observational study, consisting of 85 faculty members in the area of Human and Natural Sciences of a university. For the analysis of the sample, chi-square test and Fisher’s exact test were used. Results: 24.7% (n = 21) self-rated their health as regular/poor. (P = 0.022), the Waist/Stature ratio (p = 0.014), the level of physical activity (p = 0.050), the time in administrative positions (p = 0.026) and stress-related symptoms (p = 0.043). Conclusion: The time in administrative position and the large number of symptoms related to stress, high PW, inadequate W/S ratio and low level of physical activity were associated with negative self-rated health, recommending strategies for promotional health and prevention of stress-related diseases.